2018
DOI: 10.1002/path.5166
|View full text |Cite
|
Sign up to set email alerts
|

Obesity causes PGC‐1α deficiency in the pancreas leading to marked IL‐6 upregulation via NF‐κB in acute pancreatitis

Abstract: Obesity is associated with local and systemic complications in acute pancreatitis. PPARγ co-activator 1α (PGC-1α) is a transcriptional co-activator and master regulator of mitochondrial biogenesis that exhibits dysregulation in obese subjects. Our aims were 1) to study PGC-1α levels in pancreas from lean or obese rats and mice with acute pancreatitis; and 2) to determine the role of PGC-1α in the inflammatory response during acute pancreatitis elucidating the signaling pathways regulated by PGC-1α. Lean and ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 62 publications
(90 reference statements)
2
48
0
Order By: Relevance
“…Recently, we found that severity of acute pancreatitis in obese mice is associated with PGC-1α levels. Thus, mice lacking PGC-1α exhibited increased levels of inflammatory infiltrate in the pancreas with pancreatitis [5]. It has been previously reported that the severity of sepsis-associated acute kidney injury (AKI) correlates with PGC-1α levels in the kidney, and accordingly, lack of PGC-1α causes persistent kidney injury following endotoxemia [128].…”
Section: Pgc-1α Inflammation and Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we found that severity of acute pancreatitis in obese mice is associated with PGC-1α levels. Thus, mice lacking PGC-1α exhibited increased levels of inflammatory infiltrate in the pancreas with pancreatitis [5]. It has been previously reported that the severity of sepsis-associated acute kidney injury (AKI) correlates with PGC-1α levels in the kidney, and accordingly, lack of PGC-1α causes persistent kidney injury following endotoxemia [128].…”
Section: Pgc-1α Inflammation and Oxidative Stressmentioning
confidence: 99%
“…PGC-1α is positively upregulated when cells are exposed to oxidative stress in order to prevent oxidative damage [83]. Accordingly, the lack of PGC1α is associated with a higher susceptibility to oxidative damage in mice [5,61,84]. Interestingly, even PGC-1α heterozygote (PGC-1α (+/-)) mice failed to augment Sod2 mRNA and protein levels in liver after peritonitis induction, which led to increased levels of mitochondrial oxidized glutathione (GSSG)/reduced glutathione (GSH) ratio and protein carbonyls in these mice [85].…”
Section: Tissue-specificmentioning
confidence: 99%
See 1 more Smart Citation
“…Up-regulation of PGC-1a mitigates these parameters and can reduce atherosclerotic lesions (65)(66)(67)(68)(69). PGC-1a is readily induced by exercise (70) and caloric restriction (71); in contrast, it is down-regulated by obesity (72). miR-221-3p, along with miR-19b-3p and miR-222-3p, located in the intima of atherosclerotic vessels, could posttranscriptionally regulate PGC-1a protein expression, exerting their roles in the pathogenesis of atherosclerosis by modulating endothelial cell apoptosis (41).…”
Section: Pgc-1a Is a Target Of Mir-221-3p In Vsmcsmentioning
confidence: 99%
“…Obesity, being a proinflammatory condition, potentiates inflammation in AP, but the exact mechanism mediating this effect has not been described. In a recent issue of The Journal of Pathology , Pérez and Ruiz‐Pérez et al connected obesity and AP through the transcriptional coactivator PPARγ coactivator 1α (PGC‐1α), a master regulator of metabolic and oxidative homeostasis.…”
mentioning
confidence: 99%